2016
DOI: 10.1002/ijc.30226
|View full text |Cite
|
Sign up to set email alerts
|

Risk for congenital anomalies in offspring of childhood, adolescent and young adult cancer survivors

Abstract: Offspring of cancer survivors (CS) may be at risk for congenital anomalies due to the mutagenic therapies received by their parents. Our population-based cohort study aimed to investigate the risk for congenital anomalies in offspring of CS compared to offspring of their siblings. Using the Finnish Cancer Registry, Central Population Register, and Hospital Discharge Register, we identified hospital contacts due to congenital anomalies in 6,862 offspring of CS (early-onset cancer between 1953 and 2004) and 35,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
2
25
1
1
Order By: Relevance
“…Male survivors who received high doses of alkylating drugs during childhood are especially less likely to father a child [64,65]. Offspring of survivors diagnosed in childhood do not appear to have a higher risk of congenital abnomalities, genetic diseases, and abnormal karyotypes compared with their siblings [66][67][68][69]. Moreover, no significant difference has been observed in the risk of hospitalization between children of paediatric cancer survivors and the overall population [69].…”
Section: Effects Of Chemotherapy On Cancer Survivors' Offspringmentioning
confidence: 99%
“…Male survivors who received high doses of alkylating drugs during childhood are especially less likely to father a child [64,65]. Offspring of survivors diagnosed in childhood do not appear to have a higher risk of congenital abnomalities, genetic diseases, and abnormal karyotypes compared with their siblings [66][67][68][69]. Moreover, no significant difference has been observed in the risk of hospitalization between children of paediatric cancer survivors and the overall population [69].…”
Section: Effects Of Chemotherapy On Cancer Survivors' Offspringmentioning
confidence: 99%
“…Many survivors of childhood cancer with intact fertility worry about the potential effects of previous cancer treatment on the health of their offspring. 17 Reassuringly, decades of cumulative experience have shown that naturally conceived biological children of survivors have no increased incidence of congenital malformations, [18][19][20][21][22] genetic or chromosomal anomalies, [23][24][25] or cancer compared with sibling controls and general population data. [26][27][28][29][30][31][32][33]…”
Section: Risk Of Infertility After Treatmentmentioning
confidence: 99%
“…In the case of congenital abnormalities, the definition varies greatly -with large fluctuations in prevalence rates ranging from 1.4% [8] to 9.5% [12]. In the separate studies, only one of the twelve studies reporting on congenital abnormalities reported a higher prevalence in cancer survivors [18]. In that study, the unadjusted prevalence ratio was 1.21 (95% CI 1.03 -1.40) but after adjustment for maternal age at birth of child, parity, sex of child and birth decade of child, the adjusted prevalence ratio was 1.07 (95% CI 0.91 -1.25).…”
Section: Principal Findingsmentioning
confidence: 99%
“…Some early studies suggested an increased relative risk of congenital abnormalities in the offspring of cancer survivors [15,16]. These findings have not been confirmed in more recent analyses [9,12,17,18]. Due to the low prevalence of both cancer in children and young adults and of some pregnancy and labor complications, evaluation of these data benefits from large number of subjects being involved, giving increased statistical power.…”
Section: Introductionmentioning
confidence: 97%